Effects of innovation on productivity and poverty. Organic producers CITE Agroindustrial, Arequipa - Hinojosa Perez, Anatolia Hortencia (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The objective of this study was to determine the effects of innovation on productivity, on the level of poverty of organic producers of the CITE Agroindustry CEPRORUI of Arequipa. 202 organic producers were evaluated, taking 62 people as a sample. Techniques and instruments such as the survey, interviews with experts, documentary review and observation were used. The results of the chi-square statistical test (x2), indicate that the variables are statistically associated, where there is a degree of positive correlation between innovation and productivity, negative between innovation and poverty level. Consequently, the effects of product innovation, processes, organizations, and marketing have increased yields, income, as well as improved housing and access to basic services for organic producers.